Fracture mechanics analysis of shape memory alloys using finite elements - Şimşek, Miray. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2009., 2009)
The objective of this work is to study phase transformation and its effects on macroscopic fracture behavior of superelastic shape memory alloy, Nitinol, using finite elements. For this purpose, A 2-D edge-cracked homogenous plate is modeled using ABAQUS, stress intensity factors under ModeI loading are calculated and compared to results available in literature to verify the model and the technique used. Same analyses are performed for a 2-D edge-cracked SMA plate under plane stress conditions and UMAT/Nitinol subroutine is used to define material properties. Phase transformation zones around crack tip are investigated for different applied loads and for different crack lengths. J-integrals, energy release rates and stress intensity factors are calculated. To see the effects of material properties, a parametric study is carried out and four different cases are presented. Stress intensity factors are also calculated for a center-cracked specimen and the results are compared to the only closed-form solution available in literature. The effect of volumetric strain on fracture toughness and change in fracture toughness as a result of phase transformation are discussed in detail.
Keywords: Shape memory alloys.; Fracture mechanics.; Finite element method.